Measuring the consistency of accuracy of hand-to-eye alignment using an innovative computer-programmed device for young volleyball players - Ashoor, R. A.; Oubed, W. A.; Sabr, A. J. (Journal of Human Sport & Exercise, 2021)
The study aimed to identify the level of stability and accuracy of the compatibility between the hands and the eyes of the ballplayers for a plane according to their specializations, as well as to identify the differences between them. (12) Libero players (8) Fast players (10) High players (14) The fourth chapter included presenting and analysing the results after statistically treating them. As for the most important conclusions, the test was conducted between players and players of the team and individual games who use the right side and others who use the left side. The most important recommendations are that the trait of compatibility is a kinetic characteristic, and the higher the level of the player in this trait, the higher his level in the game, the higher his level in the game, and he must train on this trait during the training unit and make comparisons between the sexes to find out their true level and know what is distinguished from the other while identifying the variables that affect it.